THE PORTRAYAL OF FEMALE CHARACTER IN “LADY ELEANORE’S MANTLE” BY NATHANIEL HAWTHORNE - Putri Ramadhani (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2021)
This research concern with the analysis of female character in Lady Eleanore’s Mantle by Nathaniel Hawthorne. The purpose of the research is to describe the female character of Lady Eleanore’s Mantle by Nathaniel Hawthorne short stories by analyzing the main female characters to the development of the plot. This research using two methods, which are qualitative and descriptive. The problem of research is want to desribe the portrayal of female character in Lady Eleanore’s Mantle. The woman is a beautiful, rich, and has high position in her community. Always get more attention and special treatment from other people and make her became to an arrogant girl. At the end, the woman get punishment and died tragically